Učinkovine za zmanjševanje čezmerne telesne mase in zdravljenje debelosti - Kikelj, Danijel (Farmacevtski vestnik, 2010)
Currently available drug therapy of overweight and obesity is very limited, therefore development of more effective drugs has become an important goal. The two general strategies to achieve weight loss are reduction of energy intake by stimulation of anorexigenic signals or inhibition of orexigenic signals, and increase of energy expenditure. This review focuses on approved and recently removed anti-obesity drugs, as well as on new approaches for drug treatment of obesity.
Keywords: debelost; drug; fentermin; orlistat; rimonabant; sibutramin; zdravila